Wing‐fanning frequency as a releaser boosting male mating success—High‐speed video analysis of courtship behavior in Campoplex capitator, a parasitoid of Lobesia botrana. (17th January 2020) - Benelli, Giovanni; Ricciardi, Renato; Romano, Donato; Cosci, Francesca; Stefanini, Cesare; Lucchi, Andrea
Abstract: Campoplex capitator is an ichneumonid parasitoid with a narrow host range, comprising grapevine moth pests. Despite being considered one of the possible candidates for biocontrol of Lobesia botrana, knowledge about its biology is limited and mass‐rearing for commercial purposes is still lacking. This research provides a quantitative analysis of the C. capitator courtship and mating behavior. C. capitator mating sequence was analyzed by high‐speed video recordings. Main behavioral parameters, with special reference to male wing fanning and antennal tapping, were quantified and linked with mating success. Furthermore, we analyzed the occurrence of population‐level behavioral asymmetries during C. capitator sexual interactions and their impact on male success. Results showed that male wing fanning was crucial to successfully approach the female. Males achieving higher mating success performed wing‐fanning at higher frequencies over unsuccessful ones. After wing fanning, most of males palpated the female's body with their antennae, before attempting copulation. The overall mating success was >70%, with a rather long copula duration (254.76 ± 14.21 s). Male wing‐fanning was lateralized on the left at population level, while antennal tapping displays were right‐biased. Side‐biased male displays do not differ in terms of frequency and duration of their main features. This research adds basic knowledge to the C. capitator behavioral ecology. Since rearing protocols for C. capitator are being developed, male wing fanning frequency may represent a useful benchmark for monitoring mate quality over time, tackling mating success reductions due to prolonged mass‐rearing.